A CENTURY OF CHANGES IN THE NATURE AND IN THE STRUCTURE OF THE WORLD ECONOMIC SYSTEM - Kazimierz Albin Klosinski (European Scientific Journal, ESJ, 2014)
A century of changes in the world economy (1914-2014) should in fact be understood as a sequence of epochal innovations leading to a new quality of civilization. The world economic system, formed under the integrating influence of the international trade, international monetary system, international investments, international enterprises and international migrations, has changed its nature and structure during the discussed period. The changes in the nature of the world economic system are manifested by the fact that the industrial character of the world economy has taken on the features of the post-industrial economy based on the dominating role of the services sectors and knowledge. The welfare policy, as developed in the discussed century, has become the flagship of the post-industrial economies. The structural changes are manifested in the new global division of labor characterized by a greater diversification and internationalization of production. The above mentioned changes result from numerous transformations taking place in the developed countries and in the economies of the developing countries.